Application of GIS Technologies for Determination of Boundaries and Area of Epizootic Regions within Natural Plague Foci - A. A. Kuznetsov; A. M. Porshakov; A. N. Matrosov; A. A. Lopatin (Проблемы особо опасных инфекций, 2017)
Spatial indicators of epizooties in natural plague foci are used for justified planning and carrying out measures on epidemiological welfare provision for the population residing in enzootic territories. Plague affected regions are identified by real geographical coordinates of epizootic sites. Objective of the study is to develop numerical methods for determination of boundaries and area of epizootic regions according to the results of epizootiological monitoring. Materials and methods. Utilized are the digital maps of the natural plague foci, the data on epizootic points, and computer software. Results and conclusions. Buffer zones in the form of circumference of 5 km radius were established around each epizootic point with the help of computer application “ArcGIS 10.x” as a counterpart of circular extrapolation method. Resultant epizootic region over a certain season was generated by several overlapping circumferences.Evaluated were the area and extension of the region, as well as the presence of epidemiologically significant objects within its bonds.Actual positioning of the region, visualized on the focus map, is used for specified task assignment as regards carrying out of various preventive measures in this or that part of the area.